Gestation Related Gene Expression of the Endocannabinoid Pathway in Rat Placenta - Kanchan Vaswani; Hsiu-Wen Chan; Hassendrini N. Peiris; Marloes Dekker Nitert; Ryan J. Wood Bradley; James A. Armitage; Gregory E. Rice; Murray D. Mitchell (Hindawi Limited, 2015)
Mammalian placentation is a vital facet of the development of a healthy and viable offspring. Throughout gestation the placenta changes to accommodate, provide for, and meet the demands of a growing fetus. Gestational gene expression is a crucial part of placenta development. The endocannabinoid pathway is activated in the placenta and decidual tissues throughout pregnancy and aberrant endocannabinoid signaling during the period of placental development has been associated with pregnancy disorders. In this study, the gene expression of eight endocannabinoid system enzymes was investigated throughout gestation. Rat placentae were obtained at E14.25, E15.25, E17.25, and E20, RNA was extracted, and microarray was performed. Gene expression of enzymes Faah, Mgll, Plcd4, Pld1, Nat1, Daglα, and Ptgs2 was studied (cohort 1, microarray). Biological replication of the results was performed by qPCR (cohort 2). Four genes showed differential expression (Mgll, Plcd4, Ptgs2, and Pld1), from mid to late gestation. Genes positively associated with gestational age were Ptgs2, Mgll, and Pld1, while Plcd4 was downregulated. This is the first comprehensive study that has investigated endocannabinoid pathway gene expression during rat pregnancy. This study provides the framework for future studies that investigate the role of endocannabinoid system during pregnancy.